Determination of Human Resource Quality as a Determinant of Income Disparity Level in Yogyakarta Special Region Province - Andriana, Yeyen; Imaningsih, Niniek (Trunojoyo University of Madura, 2024)
This research aims to test and see the influence of Life Expectancy (AHH), Education Based on Average Years of Schooling, and Poverty Levels on Income Inequality in the Special Region of Yogyakarta Province in 2008-2022. The data used in this research is only 15 years for each variable due to limited data in previous years. Data was obtained from the Central Bureau of Statistics for the Special Region of Yogyakarta Province for 2008-2022. Data processing uses multiple linear regression analysis techniques with EViews as a statistical analysis tool. This research aims to analyze the influence of Life Expectancy (AHH) and Education Based on Average Years of Schooling on Income Inequality in Yogyakarta Special Region Province. Data analysis shows that the two variables individually have a significant positive influence on Income Disparity, according to the results of the t test which shows the probability value is lower than the 0.05 significance level. Increasing education can also increase income inequality, because the phenomenon of job preferences according to the field of education can result in unemployment. The implications of this research highlight the complexity of the relationship between education, well-being and occupational preferences in a regional context rich in cultural values.